ANALYSIS OF EXPORT AND IMPORT COMPETITIVENESS OF LEADING COMMODITIES IN SOUTHEAST SULAWESI PROVINCE, 2020–2024 - Puspa Dewangga; Caesar Muslim; Dheavivi Ayu Dian Pebrian; Miming Lestari; Anggi Yovita (Journal Economics Technology And Entrepreneur, 2025)
This study analyzes the development of export and import activities of leading commodities in Southeast Sulawesi Province and their contribution to the Regional Gross Domestic Product (RGDP) during the 2020–2024 period. A quantitative descriptive method was applied using secondary data from the Central Bureau of Statistics (BPS) and the Ministry of Trade. The results show that exports are dominated by stainless steel and ferronickel, which drive the regional economy, peaking in 2022 at USD 5.26 billion. Meanwhile, imports primarily consist of industrial raw materials, such as ferro-chromium, bituminous coal, and anthracite, which serve as inputs to metal-processing industries. The contribution of exports to RGDP increased from 34.6% in 2020 to 76.2% in 2022 before declining to 53.5% in 2024. These findings highlight the need to strengthen industrial downstreaming, diversify export products, and improve trade logistics efficiency to ensure sustainable regional economic growth.